STUDI DESKRIPTIF DINESERV WARUNG LEKO CABANG BONET MENURUT PERSEPSI PELANGGAN YANG BERDOMISILI DI SURABAYA - Angela Paramitha (Perpustakaan Universitas Surabaya, 2013)
This study aimed to identify and describe the perceptions of customers towards dineserv Warung Leko dineserv branch Bonet, Surabaya. Type of study is purely descriptive, with characteristics of the population of customers who have visited Warung Leko Bonet branch at least 2 times in the last 3 months, last at least high school education / vocational school, and population must be based in Surabaya. Research using the mean calculation processing methods. Of these methods concluded that dineserv Warung Leko scored well by customers.